Eicosanoids and cancer - Wang, Dingzhi (2010)
Eicosanoids, including prostaglandins and leukotrienes, are biologically active lipids that have been implicated in various pathological processes, such as inflammation and cancer. This Review highlights our understanding of the intricate roles of eicosanoids in epithelial-derived tumours and their microenvironment. The knowledge of how these lipids orchestrate the complex interactions between transformed epithelial cells and the surrounding stromal cells is crucial for understanding tumour evolution, progression and metastasis. Understanding the molecular mechanisms underlying the role of prostaglandins and other eicosanoids in cancer progression will help to develop more effective cancer chemopreventive and/or therapeutic agents.